Frequency of the symptoms of Polycystic Ovary Syndrome and Premenstrual Syndrome, related to academic stress in medical students of a private university in Peru: Frecuencia de la sintomatología del Síndrome de Ovario Poliquístico y el Síndrome Premenstrual, relacionado con el estrés académico en estudiantes de medicina de una universidad privada del Perú - Pantigoso Suárez, Diana Carolina (2023)
Introduction: Polycystic ovary syndrome (PCOS) and premenstrual syndrome (PMS) are prevalent. Objective: to determine the frequency of the symptoms of polycystic ovary syndrome and premenstrual syndrome and its relationship with stress in medical students. Material and methods: Cross-sectional analytical study. The study population was 322 medical students from the 1st to the 12th cycle, chosen by convenience from a private university in Trujillo. Through a google form, the "SPM" questionnaire, "the SISCO inventory of academic stress", and "the questionnaire on polycystic ovary" were applied; prior informed knowledge, it had the approval of the Bioethics Committee of the university. Results: The SOP presented a high probability of 5.28%, medium of 46.58% and low of 48.13%.The frequency of PMS in the levels, mild, moderate and high were 47.52%, 25.47% and 4 0.04% respectively. The levels of stress were: mild, moderate and deep 4.35%, 65.22% and 30.43%, respectively. A highly significant association was found between stress and SPM; stress and PCOS; p = 0.000915106 and p= 1.8589E-25 respectively Conclusions: The frequency of PMS, the high probability of PCOS and the levels of stress were high and there is a significant association between stress, PMS and PCOS. Keywords: Polycystic ovary syndrome, Premenstrual syndrome, stress, medical students (MESH).